CoreTrustSeal: From academic collaboration to sustainable services - Hervé L'Hours; Mari Kleemola; Lisa de Leeuw (IASSIST Quarterly, 2019)
National and international digital repositories must design and deliver sustainable services as a foundation for a range of scientific and data management infrastructures while reducing costs and avoiding duplication of effort. The CoreTrustSeal, launched in 2017, defines requirements and offers core level certification for Trustworthy Digital Repositories (TDR) holding data for long-term preservation. This paper traces the journey of the CoreTrustSeal through the Data Seal of Approval (DSA), ICSU World Data System (WDS), Research Data Alliance (RDA) working groups, and community engagement, towards becoming a sustainable service supporting global data infrastructure. We outline the design and delivery of the service, current activities, the benefits of certification to a range of communities, and future plans and challenges. As well as providing a historical narrative and current and future perspectives the CoreTrustSeal experience offers lessons for those developing standards and best practices, or seeking to develop cooperative and community-driven efforts which bridge data curation across academic disciplines and the governmental and private sectors.